Analisis Pembiayaan Multimanfaat Dengan Akad Murabahah Bil Wakalah Berdasarkan Fatwa DSN MUI - Khoiriyah, Ahyadatul; Miswan Ansori; Wahidullah (Rayah Al-Islam, 2025)
This study analyzes the implementation of the murabahah bil wakalah contract in multi- benefit financing at BTN Syariah KCPS Kudus and assesses its compliance with the DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000 concerning Murabahah and No. 10/DSN-MUI/IV/2000 concerning Wakalah. The method used in this study is qualitative with data collection techniques being interviews with related parties, namely Financing Service, Operation Staff, and Sub Branch Head, as well as direct observation of the contract process and supervision of implementation in the field. The results of the study indicate that the murabahah bil wakalah contract has been implemented in accordance with the sharia principles stipulated in the DSN-MUI fatwa, especially in terms of clarity of the contract, determination of selling price, and financing mechanism. However, there are several challenges faced, especially in terms of ownership of goods before selling to customers and monitoring the use of funds to ensure that they are in accordance with the objectives of the contract. As an implication, this study recommends strengthening transaction verification mechanisms, increasing transparency in ownership of goods before being sold to customers, and more effective education strategies for customers to ensure compliance with sharia principles.